DOI: 10.3990/1.9789036531511
|View full text |Cite
|
Sign up to set email alerts
|

Membrane supported scaffold architectures for tissue engineering

Abstract: Prof. Dr. J. Vienken (Fresenius Medical Care, Germany) Dr. C. Legallais (Université de Technologie, France) Author -Narasimha Murthy Srivatsa BettahalliTitle -"Membrane supported scaffold architectures for tissue engineering"PhD Thesis, University of Twente, Enschede, The NetherlandsThe research described in this thesis was financially supported by STW (Utrecht, NL) (Project number -TKG.6716)Printed by: Gildeprint Drukkerijen, Enschede, The Netherlands Cover designed by NM Srivatsa BettahalliThe front co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 75 publications
(118 reference statements)
0
0
0
Order By: Relevance
“…In literature they are described as a hepatocyte bioreactor and a medium perfusion system for three-dimensional tissue-engineered constructs. 12,13 These studies showed that the multibore hollow fiber was biocompatible. 12,13 The scaffolds were seeded with rat insulinoma cells or primary bovine chondrocytes, as a model for Islets of Langerhans, to investigate the performance of the imaging approach and optimize it for future in vivo applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature they are described as a hepatocyte bioreactor and a medium perfusion system for three-dimensional tissue-engineered constructs. 12,13 These studies showed that the multibore hollow fiber was biocompatible. 12,13 The scaffolds were seeded with rat insulinoma cells or primary bovine chondrocytes, as a model for Islets of Langerhans, to investigate the performance of the imaging approach and optimize it for future in vivo applications.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 These studies showed that the multibore hollow fiber was biocompatible. 12,13 The scaffolds were seeded with rat insulinoma cells or primary bovine chondrocytes, as a model for Islets of Langerhans, to investigate the performance of the imaging approach and optimize it for future in vivo applications. Near-infrared (NIR) wavelengths showed low scaffold signal background and deep penetration depths compared with visible wavelengths.…”
Section: Introductionmentioning
confidence: 99%